Cardiac diagnostic tests a guide for nurses - VanRiper, Sharon; VanRiper, John. (Philadelphia W.B. Saunders, 1997)
Cardiac Diagnostic Tests: A Guide for Nurses places the key diagnostic knowledge you need at your fingertips. Inside, you'll find detailed descriptions of each type of diagnostic test - explaining why the test is chosen, how it is performed, how the results are interpreted, and what care is required before, during, and after the test.
Introduction -- Electrocardiography -- Laboratory tests -- Echocardiography -- Nuclear medicine studies and positron emission tomography -- Magnetic resonance imaging and computerized tomography -- Cardiac catheterization -- Electrophysiology testing.
Includes bibliographical references and index.
Keywords: Heart -- Diseases -- Diagnosis; Heart -- Diseases -- Nursing; Heart Diseases -- diagnosis